Answer:
[tex]y=(x-3)^2-2[/tex]
Step-by-step explanation:
Given vertex of parabola [tex](3,-2)[/tex]
Where [tex](h,k)[/tex] is the vertex.
[tex](h,k)=(3,-2)\\h=3\ and\ k=-2[/tex]
Also parabola opens up.
The equation of parabola with vertex [tex](h,k)[/tex]
[tex]y= a(x - h)^2 + k[/tex]
If [tex]a>0[/tex] parabola opens up.
[tex]a<0[/tex] parabola opens down.
As the parabola opens up the value of [tex]a[/tex] will greater than zero.
Plugging vertex of parabola in equation [tex]y= a(x - h)^2 + k[/tex]
[tex]y= a(x - 3)^2 -2[/tex]
Let us plug [tex]a=1[/tex]
The equation will be [tex]y= a(x - 3)^2 -2[/tex]